Description of the larva of Catadromus lacordairei Boisduval, 1835 (Coleoptera: Carabidae), a threatened carabid, from Tasmania, Australia - Richards, Karen; Spencer, Chris P. (Zootaxa, 2019)
The carabid beetle genus Catadromus MacLeay (Coleoptera: Carabidae) is endemic to the Australasian region. Of the five currently recognised species, only one, C. lacordairei Boisduval, 1835 occurs in Tasmania, Australia, where it is listed as a threatened species on the Tasmanian Threatened Species Protection Act 1995. In the present paper, we describe and illustrate the larva of C. lacordairei, providing the first detailed larval description of a member of this genus.